STUDENT DECISION-MAKING IN STUDYING AT THE SHARIA BANKING STUDY PROGRAM AT STAI PELITA NUSA WEST BANDUNG - Mamun, Saepul; I. Tunggara, Imam; Solihin, Dadin; Sumarno, Ardawi (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2024)
Decision-making involves a thought process, in which individuals evaluate a variety of alternative options in acting, acting, and acting. Ontological promotions, costs, facilities, image, and prospects can influence students' decision-making to choose the Sharia Banking Study Program. The purpose of the study was to determine the various factors of student influence in making decisions to choose the Sharia Banking S1 Study Program at STAI Pelita West Bandung with a sample of data of 109 S1-Sharia Banking students through the path analysis method, analyzing patterns of relationships between variables that affect either directly, or indirectly between independent variables (exogenous) to bound variables (endogenous). The results of the study, reviewed from the descriptive analysis of promotion, tuition fees, educational facilities, an image of study programs, and student decision-making, are all included in the high category. The results of testing, and the cost of education, are much influenced by the effectiveness of promotion. The image of the study program directly much is determined by the promotion and cost of Education. The promotion of education costs and educational facilities to the image of the study program is relatively large, meaning that these two factors can boost the cost of education and educational facilities in supporting the image of the Islamic banking study program to increase. Promotion strategy is a key factor in increasing the cost of education, institutions, and the image of study programs, both directly and indirectly can improve student decision-making